2017
DOI: 10.1039/c6nj03701a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for regioselective ring opening of epoxides by amines under microwave irradiation using Bi(NO3)3·5H2O as a catalyst

Abstract: Bi(NO3)3·5H2O a highly efficient environmentally benign catalyst, is used for the nucleophilic ring opening of epoxides with aromatic, aliphatic and heteroaromatic amines under solvent free microwave conditions to afford the corresponding β-amino alcohols in good to excellent yields with high regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…2‐(Naphthalen‐1‐ylamino)‐2‐phenylethan‐1‐ol ( 4 g ) [30e] . Dark yellowish oil, yield: 257 mg (98 %).…”
Section: Methodsmentioning
confidence: 99%
“…2‐(Naphthalen‐1‐ylamino)‐2‐phenylethan‐1‐ol ( 4 g ) [30e] . Dark yellowish oil, yield: 257 mg (98 %).…”
Section: Methodsmentioning
confidence: 99%
“…Later on, Bhanage [38] et al reported solvent free methodology for aminolysis of epoxides catalyzed by Y(NO 3 ) ⋅ 6H 2 O at room temperature (Figure 1), but these protocols suffered from some shortcomings for longer reaction time, tedious workup, costly and hazardous catalyst. In our earlier work [39] we reported regioselective and efficient protocol for the aminolysis of epoxides treated with low toxic, inexpensive and versatile nature of catalyst i. e. bismuth(III)nitrate pentahydrate, under solvent free microwave irradiation condition. Inspired by the results obtained, we intend to make an exhaustive study of other bismuth salts to add further meaningful insight in the catalytic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric ring-opening (ARO) reaction of epoxides with amines is the most straightforward route to prepare β-amino alcohols. In recent years, several catalysts such as Lewis acids [11][12][13], metal-organic frameworks [14] and Bismuth (III) salts [15][16][17][18] have been reported for ring-opening reactions. However, these approaches usually require the use of costly reagents, high catalyst loadings, poor regioselectivity and also entail side effects, such as the rearrangement of epoxides to allyl alcohols under strong alkaline conditions or polymerization under strongly acidic conditions.…”
Section: Introductionmentioning
confidence: 99%